2021
DOI: 10.1021/jacs.1c07482
|View full text |Cite
|
Sign up to set email alerts
|

Pickering-Droplet-Derived MOF Microreactors for Continuous-Flow Biocatalysis with Size Selectivity

Abstract: Enzymatic microarchitectures with spatially controlled reactivity, engineered molecular sieving ability, favorable interior environment, and industrial productivity show great potential in synthetic protocellular systems and practical biotechnology, but their construction remains a significant challenge. Here, we proposed a Pickering emulsion interface-directed synthesis method to fabricate such a microreactor, in which a robust and defect-free MOF layer was grown around silica emulsifier stabilized droplet su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 63 publications
0
32
0
2
Order By: Relevance
“…Tian et al. reported a continuous flow reactor filled with MOF coated micelles containing the enzyme CALB [25] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al. reported a continuous flow reactor filled with MOF coated micelles containing the enzyme CALB [25] …”
Section: Methodsmentioning
confidence: 99%
“…Tian et al reported a continuous flow reactor filled with MOF coated micelles containing the enzyme CALB. [25] In other catalytic applications of MOFs, [26,27] continuousflow, packed-bed reactors [28,29] showed substantial differences to batch experiments. Therefore, investigating Enzyme@MOF systems in a flow reactor is a crucial next step towards real world applications.…”
mentioning
confidence: 99%
“…Tian et al. berichteten über einen Durchflussreaktor, gefüllt mit MOF‐beschichteten Mizellen, die das Enzym CALB enthielten [25] …”
Section: Methodsunclassified
“…1,2 Many efforts have been devoted to improving the catalytic selectivity of metal nanocatalysts. For example, nanopalladium is loaded into the pores of MOFs, [3][4][5][6][7][8][9][10][11][12] or into the channels of molecular sieves, [13][14][15] or into the apo-ferritin cage, 16 so as to form a selective catalytic system with the action of a carrier. [17][18][19] Although the selectivity of these catalytic systems did improve significantly, they struggle to compete with self-reproducible, green synthetic and recyclable biocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great interest for us to couple the high catalytic selectivity of living cells with the high activity of nano-metal catalysts, exploring the selectivity of the living cell catalytic systems, including the intracellular enzyme-like metal nanocatalysts with high activity, 23,24 and the cell membrane with high selectivity. 10,25 The LCCSs not only have high selectivity, self-replication and recyclability but also have high activity and stability due to the dispersing and stabilizing effects of intracellular proteins, 26 which might open unforeseen opportunities to achieve the multitudinous special catalytic processes that do not occur in natural catalytic systems for desirable chemical applications.…”
Section: Introductionmentioning
confidence: 99%